On groups factorizable in commuting almost locally normal subgroups - Chernikov, N. S. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We prove that an RN-group (in particular, locally solvable) G =G 1 G 2 ...G n with G i and π(G i ) ∩ π(G j ) = ⊘,i ≠j is a periodic hyper-Abelian group if the subgroupsG j are almost locally normal.